Transforming tradition: cultural essays in honour of Mukund Lath - Horstmann, Monika (Prākṛta-Bhāratī-Akādamī-granthamālā, 2013)
Mukund Lata, Indian musicologist and poet; contributed articles
Includes bibliographical references and index. - One article and some poems in Hindi (Devanagari)
Keywords: India -- Civilization; Aufsatzsammlung; Festschrift; Geschichte; Religion; Literatur; Kultur; Indien